Effect of sodium deoxycholate on cell-detachment using quantitative phase interferometry - Tan, Yi Jia (2019)
Decellularization is the process of stripping cells from the organs. There are many ways that can be used to strip cells. One of them is to use surfactants which acts as a detergent to reduce surface tension between the cell and the organ. Sodium deoxycholate is an ionic surfactant that decellularize the organ by solubilizing the cell membrane. This research uses sodium deoxycholate to study the effect it has on cell-detachment using quantitative phase interferometry imaging method. The aim of this study is to grow a fundamental understanding on the decellularization process involving surfactants commonly used in tissue engineering. Experiments were done using cells grown on sterile petri dishes. Sodium deoxycholate is minister to the cells on the petri dishes. Using quantitative phase interferometry imaging method, the cells are imaged and quantified.